Clinical and epidemiological features of tuberculosis in children and adolescents - George Jó Bezerra Sousa; Julio Cesar de Oliveira Silva; Talita Vaz de Queiroz; Lia Guedes Bravo; Gizelly Castelo Branco Brito; Aline de Souza Pereira; Maria Lúcia Duarte Pereira; Luciana Kelly Ximenes dos Santos
ABSTRACT Objective: To analyze the clinical and epidemiological features of tuberculosis in children and adolescents in an infectious diseases reference hospital. Method: A documental and retrospective study was carried out with 88 medical files in an infectious diseases reference hospital in the state of Ceará. Data were analyzed by univariate, bivariate and multivariate approaches. Results: It was found that, depending on the tuberculosis type, its manifestations may vary. The logistic regression model considered only pulmonary tuberculosis due to a number of observations and included female sex (95% CI: 1.4-16.3), weight loss (95% CI: 1.8-26.3), bacilloscopic screening (95% CI: 1.5-16.6) and sputum collected (95% CI: 1.4-19.4) as possible predictors. Conclusions: Children and adolescents present different manifestations of the disease depending on the tuberculosis type that affects them. Knowing the most common features of each condition could enhance early diagnosis and, consequently, result in adequate treatment and care.